When Europa meets Bismarck. How Europe is used in the Australian Healthfare System - Kostera, Thomas (European Studies, 2016)
What happens when the European Union sets new rules for the provision of cross-border healthcare services that were conceived for the population living on the national territory? Does Europe destabilize national social solidarity? Do actors that govern the healthcare system further or resist the Europeanization of their national healthcare system?